THE RELATIONS OF STATE AND CHURCH IN POLITICS OF MEMORY: EXPERIENCE OF UKRAINE AND POLAND REPUBLIC - Федорищак, Х. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Based on analysis of legal acts, sociological research determined the relationship between church and state in politics of memory. Analyzes legal regulation of church-state relations and the relationship of politics and religion in Ukraine and Poland. Religion throughout whole history was the noticeable factor of association of people, by a necessary component in forming of individual and collective memory. On a way to satisfaction of spiritual necessities the institute of church quite often touches those planes of public existence, that is directly or mediated related to politics. In fact, inalienable part of this institute are mention measures: liturgies, dead-offices, glorifications in canons and tropers, lectures, round table, and others like that. Therefore, depending on the object of celebration in honour a that or other measure can acquire certain political painted. A problem of memory is on crossing at once of a few sciences : political science, history, psychology, religious studies. For this reason, memorial practices are the constituent of wide concept “policy of commemorate”. In the early 80s the government and the communist parties of several countries, including Ukraine and Poland, began to liquidate barriers in the field of religious freedom. The result was the revival of religious life, which led to the growth of religious communities, building new places of worship, the liberalization of laws on freedom of conscience and activity of religious organizations. High authority and trust in society to the institute of Church (as a guarantor of justice, оберега of moral, cultural and historical traditions) converted him into one of influential factors of modern political process, means of harmonization of frame of society.